PERAN PENTING PENDIDIKAN KARAKTER BAGI ANAK UNTUK MENINGKATKAN KUALITAS KELUARGA DI DESA SIGAPOKNA KECAMATAN SIBERUT BARAT, KAB.KEPULAUAN MENTAWAI - JAE123 JAE123; Fifi Yasmi; Azwar Azwar (STKIP PGRI Sumatera Barat, 2021)
Community service, on the socialization of the important role of education for children to improve the quality of families in Sigapokna Village, West Siberut District, Mentawai Islands Regency, is based on findings in the field that there are still many children who have dropped out of school and some of them have never received education at school since their age. In addition, parents have never received an education at school, so that it is reflected in the quality pattern of community life in families. The problem here is that the people in Sigapokna village based on information from the headman are still many people who do not understand the essence of education, the purpose of education and the role of education for their children to improve the quality of life in the family. The objectives of Community Service activities are 1) to provide understanding through socialization about the importance of education to improve the quality of families, 2) to provide opportunities in the form of responses from the Sigapokna Village community after the Community Service Activities were held. The method of community service activities is through the following stages 1) needs analysis, 2) work plans, 3) implementation of activities, 4) evaluation. The results of community service activities with the target population in the Sigapokna Village community by providing an understanding through the socialization of the importance of education, the goals of education, the role of education in improving the quality of families, and questions and answers about education that are attended by the community in the form of parents, children, village officials, there are approximately 50 heads of local families who have received a positive response from the community and the community's understanding is quite good.